PENERAPAN KETERAMPILAN BERPIKIR KREATIF TERHADAP HASIL BELAJAR (ANALISIS DESKRIPTIF PADA SISWA SDN 01 GALUR) - Dea Nurshadrina Sausan; Petrus Paulus Mbette Suhendro, Uswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study provides a descriptive analysis of the level of creative thinking skills and learning outcomes of fifth-grade students in the subject of Environmental and Cultural Education of Jakarta at SDN 01 Galur. Data were obtained from two sources: creative thinking skill test results and academic achievement scores of 47 students as research subjects, as well as observation data collected through teacher-completed questionnaires to illustrate classroom learning conditions. The study employed a quantitative approach with a descriptive research design. The results showed that students’ learning outcomes were generally in the good category, with an average score of 84.77; 74.5% of students were in the moderate category, 21.3% in the high category, and 4.2% in the low category. The implementation of strategies to develop creative thinking skills by teachers was rated very good, with an average score of 4.78 on a 5-point scale. The fluency dimension received the highest score (4.92), while originality and sensitivity to problems received the lowest (4.67). Findings indicate that students with higher creative thinking skills tend to achieve better academic outcomes. The study concludes that while the application of creative thinking skills supports student learning outcomes, further enhancement is needed in the areas of originality and sensitivity to problems.